2015
DOI: 10.2166/wrd.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cryptosporidium oocyst and Giardia cyst removal efficiency from urban and slaughterhouse wastewater treatment plants and assessment of cyst viability in wastewater effluent samples from Tehran, Iran

Abstract: Five municipal and domestic wastewater treatment plants, most of which had secondary treatment systems formed by activated sludge, were studied during 2013-2014 in Tehran. The study was done in order to evaluate their efficiency in terms of removal of Cryptosporidium and Giardia by (oo)cyst recovery in effluent samples using immunofluorescence with monoclonal antibodies. Results showed that mean concentrations of cysts in the influent samples always outnumbered mean concentrations of oocysts (883.3 ± 4,16.7-3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
2
7
0
1
Order By: Relevance
“…Cryptosporidium was identified in 4 out of 707 school children from Turkey (0.6%); all the isolates belonged to the C. parvum bovine genotype (34). The current results are consistent with the reports from Saudi Arabia, Iran, Kuwait, and Turkey (8,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cryptosporidium was identified in 4 out of 707 school children from Turkey (0.6%); all the isolates belonged to the C. parvum bovine genotype (34). The current results are consistent with the reports from Saudi Arabia, Iran, Kuwait, and Turkey (8,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 92%
“…The rate of positivity was lower in PCR than in microscopic examination. Previous studies also reported similar findings, which might be attributed to DNA inadequacy due to the low number of oocysts in stool samples (26)(27)(28).…”
Section: Discussionsupporting
confidence: 69%
“…It is estimated that in the USA 748,000 cases of human cryptosporidiosis occur annually [3]. Residents of and travelers to developing countries may be at greater risk of infection due to poor water treatment and food sanitation [4, 5]. Cryptosporidiosis typically induces self-limiting diarrhea in immunocompetent individuals, but the infection can be severe and life-threatening in immunocompromised subjects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the prevalence of parasites was 21.2% in Tehran in 2008 (5), 74.6% in Tonekabon in 1992 (23), %25 in Mazandaran in 2005 (24), and %19.66 in Kirkuk in 2015, by formalin-ether concentration and Ziehl-Neelsen staining (25) that can assume the proportions of contamination were somewhat similar considering the year and cities. Although the spread of parasites was very high in the past based on the overall prevalence of intestinal parasites in wastewaters (26) but today it has declined due to the rising levels of health. Accordingly, the data gathered from this study shows no helminthic infection, which is probably due to the upgrade of urban lifestyles and the improvement of public health and environmental sanitation (27).…”
Section: Discussionmentioning
confidence: 99%